Circulating heparan sulfate fragments mediate septic cognitive dysfunction - Hippensteel, Joseph A. (J Clin Invest, 2019)
Septic patients frequently develop cognitive impairment that persists beyond hospital discharge. The impact of sepsis on electrophysiological and molecular determinants of learning is underexplored. We observed that mice that survived sepsis or endotoxemia experienced loss of hippocampal long-term potentiation (LTP), a brain-derived neurotrophic factor–mediated (BDNF-mediated) process responsible for spatial memory formation. Memory impairment occurred despite preserved hippocampal BDNF content and could be reversed by stimulation of BDNF signaling, suggesting the presence of a local BDNF inhibitor. Sepsis is associated with degradation of the endothelial glycocalyx, releasing heparan sulfate fragments (of sufficient size and sulfation to bind BDNF) into the circulation. Heparan sulfate fragments penetrated the hippocampal blood-brain barrier during sepsis and inhibited BDNF-mediated LTP. Glycoarray approaches demonstrated that the avidity of heparan sulfate for BDNF increased with sulfation at the 2-O position of iduronic acid and the N position of glucosamine. Circulating heparan sulfate in endotoxemic mice and septic humans was enriched in 2-O– and N-sulfated disaccharides; furthermore, the presence of these sulfation patterns in the plasma of septic patients at intensive care unit (ICU) admission predicted persistent cognitive impairment 14 days after ICU discharge or at hospital discharge. Our findings indicate that circulating 2-O– and N-sulfated heparan sulfate fragments contribute to septic cognitive impairment.